European Sustainability Reporting Standards: Lack of Progress, Alignment, and Harmonization in Western Balkans - Ivana Ljutić; Benina Veledar; Amra Gadžo; Mila Knežević (Economic Analysis, 2024)
This paper aims to investigate the status of alignment and harmonization of corporate reporting in Western Balkans (WB) countries with the European Sustainability Reporting Standards (ESRS). Specifically, the research will focus on understanding the extent to which WB countries have initiated the adoption of ESRS, particularly in the context of the Corporate Sustainability Reporting Directive (CSRD) that mandates its use for companies within the European Union (EU) and its branches. The paper will compare the achieved level of sustainability reporting in Western Balkan countries with other countries located in Europe that are not members of the European Union. Despite the mandatory nature of ESRS for companies within the EU, our preliminary analysis indicates a lack of progress in the alignment and harmonization process among the WB countries. Western Balkan countries are also lagging behind, compared to other non-EU member countries, such as Switzerland and Norway, which have been selected for comparative analysis. The research seeks to uncover the reasons behind this lag and to explore the potential challenges faced by companies in the WB region in implementing these standards. It is crucial to understand the current state of sustainability reporting practices in WB countries and the challenges faced in aligning with ESRS. It will provide valuable insights for policymakers, businesses, and stakeholders on the necessary steps to enhance sustainability reporting practices in the region and foster alignment with international standards.
Keywords: 330; European Sustainability Reporting Standards; Corporate Sustainability Reporting Directive; Sustainability Reporting Practices; Western Balkans countrieses